Validation of hip osteoarthritis diagnosis recording in the UK Clinical Practice Research Datalink - Ferguson, R; Prieto-Alhambra, D; Walker, C; Yu, D; Valderas, J; Judge, A; Griffiths, J; Jordan, K; Peat, G; Glyn-Jones, S; Silman, A (Wiley, 2018)
Purpose: The diagnosis of hip osteoarthritis is subject to several uncertainties, especially in primary care. The aims of this study were to determine (i) the diagnostic accuracy of coding of hip osteoarthritis by primary care physicians in the UK Clinical Practice Research Datalink (CPRD), (ii) the relative influence of radiographic and clinical parameters on diagnostic accuracy, and (iii) the accuracy of the diagnosis date. Methods: An extract of all patients aged over 65 years, with a Read code for hip osteoarthritis listed between January 1995 and December 2014, was obtained from CPRD. A random sample was selected of 170 participants. A questionnaire concerning data in medical records on relevant clinical and radiographic criteria used to establish the diagnosis of hip osteoarthritis was distributed to primary care physicians of participants. Using diagnostic criteria, we formulated thresholds for diagnosis based on clinical, radiographic and combined grounds. Results: 119 completed questionnaires were returned (70% response rate). The positive predictive value (PPV) of hip osteoarthritis codes, based on radiological criteria, was 79.8%. The PPV, based on clinical criteria, was 79.0%, with substantial but not complete overlap. Overall 12% of diagnoses were not confirmed. In 42% of cases, there was disparity between date of diagnosis in CPRD and the medical record. Median difference in date was +/-425 days (interquartile range, 18-1448 days). Conclusions: Despite the difficulties in reaching a diagnosis of hip osteoarthritis in primary care, CPRD Read codes have a sufficiently high PPV for most research uses. However, the accuracy of diagnosis date may not be as reliable.